Emotions in the workplace and behavioural consequences: are there any differences between older and younger workers? - Aniceto, Juliana Soares Ribeiro (2016)
Scholars have studied the influence of age in work-related behaviours (e.g., Ng & Feldman, 2008). But these studies focused mainly in broad environmental characteristics while our study focuses on age differences in the context of what happens in the workplace on a daily basis. Thus, we framed our study within the Affective Event Theory (Weiss & Cropanzano, 1996), which postulates that employees’ work behaviours result from their emotional experiences in the workplace and focuses on work events as the proximal cause of affective reactions. We conducted a diary study on a sample of about 160 workers. They filled in a questionnaire at the end of each working day, reporting two events and how they felt about them. They also reported about their behaviours at work during that day: one positive (job crafting) and one negative (incivility). We found that positive emotions with high and low arousal positively correlated with job crafting; and negative emotions with high arousal but not those with low arousal positively correlated with uncivil behaviours. Age moderated some of these relationships, and interactions revealed interesting differences between younger and older workers, with high arousal positive emotions being more strongly associated to crafting in younger workers and a tendency to a stronger association between high arousal negative emotions and incivility in older workers. These findings suggest that employees of different age may manage emotions in a different way and have important implications for training on emotion regulation strategies.